Extrusion molding method of reproducible low-temperature SCR (Selective Catalytic Reduction) catalyst

By using thermoplastic plastics as carrier materials and employing a hot extrusion molding process to prepare low-temperature SCR catalysts, the problems of complex catalyst preparation, easy damage, and difficulty in regeneration have been solved, achieving efficient and environmentally friendly catalyst regeneration and recycling.

CN120900703APending Publication Date: 2025-11-07ZHEJIANG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510982875.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-16
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing SCR catalysts have complex preparation processes, low mechanical strength, are easily damaged, are difficult to transport, are difficult to regenerate after deactivation, and their recycling and disposal cause environmental pollution, serious waste of resources, and high costs.

Method used

Thermoplastic plastics are used as carrier materials to prepare low-temperature SCR catalysts through hot extrusion molding, which simplifies the preparation process, increases the pore structure, and enables the regeneration and recycling of the catalyst.

Benefits of technology

It improves the mechanical strength of the catalyst, reduces the risk of damage during preparation and transportation, simplifies the regeneration process, reduces environmental pollution and resource waste, and improves the yield and recycling rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120900703A_ABST
    Figure CN120900703A_ABST
Patent Text Reader

Abstract

The invention relates to a method for extrusion molding of a renewable low-temperature SCR catalyst, and the low-temperature SCR catalyst comprises a thermoplastic which forms a carrier skeleton of the low-temperature SCR catalyst; the low-temperature SCR catalytic active component is dispersed and compounded in a carrier framework formed by the thermoplastic plastic and is supported by the carrier framework; the method comprises the following steps: (1) mixing low-temperature SCR catalytic active component powder and thermoplastic plastic powder to obtain a mixture capable of being subjected to extrusion molding; (2) putting the mixture into an extrusion molding machine, and melting to form a molten mixture; (3) the molten mixture is subjected to extrusion molding through a matched die opening of an extrusion molding machine, and an extrusion molding blank is obtained; and (4) the extrusion molding blank is cooled and selectively processed, the molded low-temperature SCR catalyst is obtained, and the low-temperature SCR catalyst can be regenerated through re-extrusion molding.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of SCR catalysts, and in particular to a fine SCR denitration catalyst and system for nitrogen oxides (NO x ), a structure, configuration, and corresponding process method. More specifically, the present application relates to a method of extrusion molding of a regenerable low-temperature SCR catalyst. BACKGROUND

[0002] Nitrogen oxides (NO x ) are one of the most major atmospheric pollutants at present, and their excessive emission not only seriously threatens human health, but also causes a series of environmental problems. At present, the proportion of flue gas NO x emission in non-electricity industries in China is increasing year by year, and achieving flue gas emission reduction in non-electricity industries is the focus of atmospheric pollution prevention and control work at the present stage.

[0003] Research and practice have found that ammonia-selective catalytic reduction (NH3-SCR) is the most mature technology for controlling NO x emission at present, and is one of the best technologies for controlling NO x emission, and the catalyst is the core of the SCR technology.

[0004] At present, the mainstream commercialized SCR denitration catalyst is a vanadium-based monolithic honeycomb catalyst (V2O5-WO3-TiO2), and its catalyst molding technology includes molding of monolithic honeycomb, plate, and corrugated plate, and is mainly prepared using titanium white powder as the paste material. Not only is the preparation process complex, but also it cannot tolerate errors. Once the molding process deviates from the optimal working condition of the molding process, the catalyst cannot meet the use requirements and is discarded. Moreover, the catalyst is prone to breakage during transportation, resulting in product loss. In addition, due to the large density of this type of vanadium-based catalyst, it is difficult to apply it in equipment scenarios such as ships and cars, which have strict requirements on the weight of the catalyst.

[0005] In addition, the desired denitration temperature of flue gas of large-scale non-fire power plant, cement kiln, industrial boiler and the like is mostly below 300°C. The existing low-temperature denitration catalyst is easily affected by fly ash, SO2, H2O and the like in the actual production operation process, leading to rapid deactivation of the catalyst and inability to be used normally for a long time. The used catalyst (which cannot meet the denitration requirements due to wear or deactivation and the like) is generally discarded directly, which not only wastes resources but also easily causes environmental pollution by being discarded at will. Although there are currently some studies on cleaning and regeneration of the catalyst, such as cleaning by ultrasonic cleaning and then acid / alkali washing and the like to restore the activity. However, in the production process of the existing technology, on the one hand, the cost of cleaning and regeneration of the catalyst is relatively high (about 40% of the price of a new catalyst, and the chemical life is 80% of that of a new catalyst), and the catalyst after multiple services cannot be recycled, which is not a recycling method with economic and environmental benefits. On the other hand, the chemical cleaning process generally inevitably causes pollution. In other words, the disposal and recycling of the catalyst also causes more costs, more complex post-treatment and more serious environmental pollution and the like.

[0006] The technology of loading a catalyst with a noble metal base by impregnation method, although it is beneficial to the recovery and utilization of the noble metal component to a certain extent, still has other losses in the extraction and filtration process, so that the noble metal active substance cannot be completely recovered. Moreover, the recovery process still causes a large amount of wastewater, part of toxic gas and only a low recovery rate, and the process method needs to be further improved.

[0007] The existing vanadium-based catalyst (V2O5-WO3TiO2) has problems of complex preparation process (calcination for 20-30 days is needed), low mechanical strength (easy to be broken during transportation), difficulty in regeneration (acid / alkali washing is needed, and the cost is high) and environmental pollution and the like. In addition, the low-temperature denitration catalyst is easily poisoned by SO2 and H2O, and the disposal cost of the discarded catalyst is high and the environment is polluted.

[0008] The advanced preparation technology and regeneration technology of the industrial denitration catalyst after deactivation are still a big problem to be solved for the denitration catalyst at present.

[0009] In the actual production and application of enterprises, the yield of catalyst preparation, breakage during transportation and deactivation of the catalyst in the actual working environment are difficult to avoid, and there is a long-term demand in the industry that the catalyst can be operated stably, with high performance and high reliability, for a longer time at a lower price. However, the current preparation and regeneration technology cannot make the catalyst operate at a relatively low operating cost and always maintain a relatively high catalytic activity.

[0010] Moreover, the spent catalysts cannot be easily disposed of in an environmentally friendly manner because they contain harmful substances such as heavy metals, which can easily enter the environment during loading, transportation, storage, and disposal, and then harm the environment and the health of living beings (including humans) through contact, inhalation, and food chain, and even cause cancer. Some spent catalysts also contain toxic components such as arsenic trioxide, arsenic pentoxide, chromium trioxide (as an example, not a common toxic component in denitration catalysts, can be replaced by vanadium pentoxide, a common component in denitration catalysts), and the like. If not properly disposed of, they will occupy space, pollute water and soil, release harmful gases, and increase air particulate matter. If properly disposed of to meet environmental and legal requirements, the high cost of materials, equipment, and processes required to dispose of the waste makes it essentially impractical for industrial use. The above chemical waste catalysts, including the above-mentioned spent catalysts, cannot be treated as general solid waste and must be entrusted to professional units with hazardous waste operating permits for recycling, utilization, and disposal to prevent environmental risks and ensure health and safety.

[0011] A Chinese patent application for invention with publication number CN117019136A, filed by the same inventor as this application on July 28, 2023, discloses a monolithic low-temperature manganese / cerium honeycomb denitration catalyst, which is prepared by using cerium dioxide (CeO2) and manganese oxide (MnO x ) as the main active components, titanium dioxide (TiO2) as the paste material, and adding a structure aid, and using an extrusion method. The catalyst was evaluated for catalytic activity and SO2 poisoning resistance by simulating the test environment of actual industrial flue gas. Experimental data show that the catalyst exhibits excellent low-temperature denitration activity and SO2 poisoning resistance, and can achieve removal of nitrogen oxides in low-temperature flue gas in actual industrial applications.

[0012] However, the existing catalyst preparation process uses inorganic materials such as TiO2 as the paste material, which is prone to sintering and will lose adhesion after multiple calcinations, making it impossible to use normally; the yield of the catalyst, damage during transportation, and deactivation of the catalyst in actual working conditions are difficult to avoid. The TiO2 material after multiple calcinations will reduce the mechanical strength of the formed catalyst and damage the structure, resulting in the catalyst being scrapped due to inability to use. Moreover, the mechanical strength of the catalyst prepared using TiO2 as the paste material is limited, and the catalyst is brittle, which can easily cause damage and breakage during transportation and use.

[0013] In addition, in the recycling and disposal of spent catalysts, such as catalyst regeneration and hazardous waste disposal, the recovery of active components from a large amount of TiO2 requires a large amount of energy, resulting in a large amount of energy waste and environmental pollution problems.

[0014] In summary, the catalyst regeneration and recycling treatment technology in the prior art has high difficulty and cost, and the technical effect and economic benefit are not good, so it is not widely used and has a bleak prospect; the treatment of hazardous waste catalyst in the prior art is easy to cause resource waste and environmental pollution; the active substance extraction technology of the catalyst in the prior art, such as hydrometallurgy, pyrometallurgy and the like, has a complicated process, high energy consumption and long time consumption; the cleaning and active substance reloading (loading) of the catalyst in the prior art during regeneration not only have a complicated process step, but also greatly reduce the mechanical strength of the final regenerated catalyst product and the regenerated catalytic performance; the paste remolding of the catalyst in the prior art in terms of regeneration and waste treatment affects the mechanical strength, and the hazardous waste needs special treatment.

[0015] Therefore, based on at least the above, there is a continuous need in the industry to innovate and create in the related preparation, material, structure, molding, regeneration and the like of the SCR catalyst, and to improve the existing catalyst molding and the like technical mode. It is desirable to innovatively improve or realize a repeatedly molded, conveniently post-processed and material recycled, regenerated and recycled molded catalyst and its preparation process, so as to alleviate or even overcome the defects of the prior art, and to realize more beneficial technical effects and technical progress.

[0016] The information included in this Background section of the specification, including any references cited herein and any description or discussion thereof, is included for technical reference purposes only and is not considered part of the subject matter that delimits the scope of the present application. SUMMARY

[0017] The present application is proposed in view of the above and other more ideas.

[0018] The inventors of the present application surprisingly found through research and repeatedly tested and verified that the polymer (as a substrate / carrier / skeleton) supported catalyst can be regenerated and reused. The present application proves through research and testing that the polymer substrate (or carrier / skeleton) supported catalyst can be regenerated by a simplified remolding process suitable for industrial scale production, realize multiple uses, greatly reduce material and production costs, and greatly reduce or even substantially eliminate negative impacts on the environment.

[0019] One of the purposes of the present application is to provide a method for (hot) extrusion molding of a regenerable low-temperature SCR catalyst, which uses a thermoplastic plastic as a carrier skeleton and contains a low-temperature SCR catalytically active component dispersed and supported in the carrier skeleton formed by the thermoplastic plastic. The method of the present application aims to realize the preparation, remolding and regeneration of the low-temperature SCR catalyst through a hot extrusion molding process.

[0020] The inventors of the present application have surprisingly found that the present application can use a thermoplastic catalyst molding process, using thermoplastic materials instead of TiO2or the like as the skeleton (carrier) material of the catalyst; at the same time, the powder catalyst component can be used as a binder for thermoplastic materials to help the various components / structures of the molded thermoplastic-based SCR catalyst to be better bonded and combined together. Ultimately, through the concept and technology of the present application, the powder catalyst thermoplastics are first molded and repeatedly molded into an industrial-grade catalyst with substantially stable and unchanged catalyst activity, stable surface physical and chemical properties, strong and light, and can be repeatedly molded and regenerated, which can replace the existing low-temperature denitration catalyst, and which can be applied to a wide range of applications, including ships, automobiles, thermal power plants, incineration plants, cement plants, gas scrubbing equipment, etc. that require lightweight catalysts.

[0021] According to an aspect of the basic application concept of the present application, a low-temperature SCR catalyst is provided, in which thermoplastic plastic is used to replace the traditional carrier material, such as TiO2, as the traditional skeleton (carrier) material, the preparation process is simplified through molding processes such as thermoplastic / thermopressing / extrusion, etc., and the pore / channel structure of the catalyst can be selectively increased by using a pore-forming agent. The low-temperature SCR catalyst can be regenerated by remolding after crushing after deactivation, achieving regeneration and recycling.

[0022] Some important aspects of the inventive concept of the present application are further described as follows:

[0023] (1) Thermoplastic plastic can be used to replace traditional carrier materials such as TiO2as the carrier skeleton material of the catalyst, simplifying and facilitating the preparation process and regeneration process of the catalyst.

[0024] The industrial denitration catalyst (nitrogen oxides (NO xGenerally, TiO2 and other materials are used as the main paste material, and active components are mixed into the mud during the molding process or are impregnated into the support material after the preparation of the support material, and then the finished catalyst is obtained after calcination and cutting. The calcination process causes the active substance to precipitate from the solution and also causes the support material to sinter and thus adhere more closely together. The production of a batch of catalysts requires processes such as mixing, kneading, aging, extrusion, drying, calcination, and cutting, which takes about 20-30 days. The present application uses thermoplastic plastic as the carrier skeleton material instead of the existing process, which only needs to mix thermoplastic powder and catalyst powder, and then perform a thermoplastic process in a mold. Due to the special surface properties of the plastic material, there is almost no mold sticking, and the desired monolithic catalyst material can be obtained from the raw materials in a very short time. The preparation by hot pressing method requires even shorter time. The method reported in the present application is limited by the hot melting temperature of the plastic material, which is lower than the calcination temperature of TiO2 material, and the heating time is shorter, and there is no need for a drying process, and the integrated rapid forming is achieved.

[0025] (2) The low-temperature denitration catalyst is loaded on the polymer material (i.e. thermoplastic plastic material) to perform integrated monolithic forming, thereby improving the mechanical strength of the monolithic catalyst.

[0026] The traditional process for preparing industrial catalysts generally uses TiO2 and other materials as the main paste material, which has a certain mechanical strength. However, different denitration catalysts use different active components, and the addition of active components can improve the catalytic activity of the catalyst, but too much active component will reduce the adhesion of the TiO2 paste, leading to embryo breakage, damage, and other problems during the drying process. Even if there is no breakage or cracking during the preparation process, there is still a probability of catalyst breakage and damage after calcination due to uneven heating and excessive active component in some areas. More likely, the catalyst prepared from TiO2 and other materials is prone to crushing and collision during transportation, resulting in breakage and damage. In addition, catalysts with insufficient mechanical strength will collapse and break due to excessive flue gas flow rate during use, and can no longer be used.

[0027] The preparation method using thermoplastic plastic as the carrier skeleton material introduced in the present application can use thermoplastic plastic material as the main body of the catalyst, which has stable physical and chemical properties and excellent mechanical strength. The catalyst can maintain the integrity of the catalyst during normal transportation and use, and can withstand greater flue gas pressure drop. Moreover, the preparation process does not require long-time drying and calcination, but only one thermoplastic process, which greatly simplifies the process flow, reduces the possibility of low yield caused by the process flow, and allows waste catalysts caused by misoperation to be remolded, saving resources.

[0028] In addition, various thermoplastics can be used to support the catalyst material stably and smoothly because their softening temperatures are higher than the working temperature window of the catalyst.

[0029] (3) The addition of pore-forming agents provides more pore structures for the catalyst

[0030] During the thermoplastic molding process, bubbles and cavities are generated due to uneven heating in the mold, which is undesirable in the preparation of plastic parts, but is desirable in the preparation of catalysts. The bubbles and channel structures can effectively increase the specific surface area and expose more catalyst active sites, thereby improving the catalytic activity. On this basis, we added a pore-forming agent during the thermoplastic process and increased the water washing / solution immersion process to remove it (e.g., by dissolution), so that the final product can have more pore structures.

[0031] (4) Simplify the catalyst regeneration process, and change the catalyst from waste to recycling.

[0032] The main reasons for catalyst deactivation are fly ash blocking the catalyst pores and the catalyst being affected by SO2 and H2O, leading to catalyst deactivation. For deactivated catalysts, we can simply clean them by washing off the fly ash and deposited ammonium sulfate salt components on the surface of the catalyst, then physically crush the molded catalyst into powder, and then perform the thermoplastic molding process again. During the crushing process, all the crushed powder samples are collected, and during the reshaping process, only a small amount of catalyst powder needs to be added. After reshaping, the sample size hardly changes, the catalytic activity does not decrease, and the catalyst can almost be recycled.

[0033] (5) Change of substrate material to make the catalyst resistant to water poisoning.

[0034] Polymer materials can be used as catalyst carriers to solve the problem of water poisoning due to their stable physical and chemical properties and non-wetting surfaces. In other catalytic reactions, polymer substrates can effectively promote the rapid departure of water and improve reaction activity. Physical mixing of catalyst powder and hydrophobic polymer materials has been proven to improve the water poisoning resistance of the catalyst. This application uses thermoplastics as catalyst carrier materials. After the catalyst powder and thermoplastics are thoroughly mixed, for example, thermoplastic molding, there may be an immersion process during preparation, but it does not affect the catalytic activity of the catalyst because the hydrophobic polymer matrix material enables the catalyst to have good water poisoning resistance.

[0035] According to the concept of one aspect of the present application, there is provided a method for extrusion molding of a regenerable low-temperature SCR catalyst, the low-temperature SCR catalyst comprising: a thermoplastic plastic forming a carrier skeleton of the low-temperature SCR catalyst; a low-temperature SCR catalytically active component dispersed in and supported by the carrier skeleton formed by the thermoplastic plastic; the method comprising the following steps: (1) mixing a low-temperature SCR catalytically active component powder with a thermoplastic plastic powder to obtain an extrusion-moldable mixture; (2) loading the mixture into an extrusion molding machine to melt and form a molten mixture; (3) extrusion molding the molten mixture through a matched die of the extrusion molding machine to obtain an extrusion molding blank; (4) cooling the extrusion molding blank and optionally processing to obtain a molded low-temperature SCR catalyst, wherein the low-temperature SCR catalyst is capable of being regenerated by re-extrusion molding.

[0036] According to one embodiment, the temperature of the melting is in the range of 200-400°C, preferably in the range of 300-320°C.

[0037] According to one embodiment, the method further comprises a process of adding at least one of a pore-forming agent, a foaming agent and a plasticizer in the extrusion-moldable mixture in the step (1).

[0038] According to one embodiment, the pore-forming agent is selected from at least one of NaCl, CaSO4, (NH4)2CO3 and carbon powder.

[0039] According to one embodiment, the method further comprises a step of cleaning the extrusion molding blank.

[0040] According to one embodiment, the processing in the step (4) comprises cutting processing on the cooled extrusion molding blank.

[0041] According to one embodiment, the shape of the molded low-temperature SCR catalyst has at least one of the following shapes: granular, plate-like, sheet-like, round pipe-like, round rod-like, square pipe-like, square rod-like and regular solid block-like.

[0042] According to one embodiment, the method is applicable to extrusion molding of thermoplastic plastics of at least one of PEEK, PFA, PPS, PTFE, PBT, PEI, PES, PCTFE, ETFE, PAI, PBI, PI, FEP, PPA, PSU, PPSU, PE, PP, fluororubber (FKM), silicone rubber (VMQ) and nylon (PA).

[0043] According to one embodiment, the method further comprises a step of regenerating the deactivated low-temperature SCR catalyst by re-extrusion molding.

[0044] According to an embodiment, the step of regenerating comprises: pre-treatment of the deactivated low-temperature SCR catalyst before regeneration, the pre-treatment comprising cleaning and crushing to obtain an extrusion-regeneration material; re-extrusion of the extrusion-regeneration material, wherein the regeneration of the deactivated low-temperature SCR denitration catalyst is achieved simultaneously with the re-extrusion.

[0045] According to an embodiment, the re-extrusion comprises at least the steps (1) to (4).

[0046] According to an embodiment, at least one of a low-temperature SCR catalytically active component powder, a thermoplastic plastic powder, and a pore-forming agent or a foaming agent is supplemented in the mixture before the re-extrusion.

[0047] According to an embodiment, the carrier skeleton of the low-temperature SCR catalyst prepared by the method of extrusion has a self-supporting configuration before and after re-extrusion, thereby enabling the low-temperature SCR catalyst to have a self-supporting configuration without external support within a set working temperature range.

[0048] According to another aspect of the present application, there is provided a low-temperature SCR catalyst capable of being reformed for regeneration, the low-temperature SCR catalyst comprising: a carrier skeleton of thermoplastic plastic, wherein the carrier skeleton of thermoplastic plastic has a shape selected from at least one of a flat plate, a corrugated plate, a honeycomb, a particle, a cloth, a tube, a rod, a mesh, and a porous sponge; and a low-temperature SCR catalyst active part complexed on or in the carrier skeleton and supported thereby, wherein the low-temperature SCR catalyst is capable of being regenerated by reformation of the carrier skeleton of thermoplastic plastic into one of a flat plate, a corrugated plate, a honeycomb, a particle, a cloth, a tube, a rod, a mesh, and a porous sponge.

[0049] According to an embodiment, the low-temperature SCR catalyst active part comprises a low-temperature denitration catalytically active material.

[0050] According to an embodiment, the low-temperature denitration catalytically active material comprises at least one of a Mn / Ce catalytic material, a V-based catalytic material, or a Cu-based catalytic material.

[0051] According to an embodiment, the carrier skeleton has an internal porous structure.

[0052] According to an embodiment, the internal porous structure accounts for more than 10% of the volume percentage of the carrier skeleton.

[0053] According to an embodiment, the low-temperature SCR catalyst active part is complexed in the carrier skeleton in the form of dispersed particles.

[0054] According to an embodiment, the low-temperature SCR catalyst active part is coated in the form of a thin film on the carrier skeleton.

[0055] According to an embodiment, the low-temperature SCR catalyst has an operating temperature below 300°C.

[0056] According to an embodiment, the thermoplastic is selected from at least one of PEEK, PFA, PPS, PTFE, PBT, PEI, PES, PCTFE, ETFE, PAI, PBI, PI, FEP, PPA, PSU, PPSU, PE, PP, fluoroelastomer (FKM), silicone rubber (VMQ) and nylon (PA).

[0057] According to an embodiment, the low-temperature SCR catalyst carrier skeleton has a self-supporting configuration both before reshaping and after reshaping, thereby enabling the low-temperature SCR catalyst to have a self-supporting configuration without external support in a set operating temperature range.

[0058] The present application overcomes many inherent technical defects of the conventional technology, including: overcoming the great waste and high cost of catalyst modules caused by the easy deactivation, inability to reshape and regenerate of conventional catalysts / modules; the environmental negative impact and environmental pollution caused by the disposal of conventional catalysts / modules; overcoming the length, complexity and high cost of the conventional production process and steps of conventional catalysts / modules; the lightweight catalyst modules of the present application replacing the heavy conventional catalysts / modules, reducing the difficulty of disassembly and transportation of conventional catalysts / modules, etc.

[0059] Further other embodiments of the present application can also achieve other advantageous technical effects not listed one by one, some of which are described below, and which can be expected and understood by those skilled in the art after reading the present application. BRIEF DESCRIPTION OF DRAWINGS

[0060] The above-mentioned features and advantages of the embodiments, and other features and advantages of the embodiments, as well as ways of realizing them, will be more apparent and can be better understood by referring to the following description in conjunction with the accompanying drawings, in which:

[0061] Figure 1A and Figure 1B are respectively a honeycomb catalyst product and a pellet catalyst product, for example prepared by a thermoplastic molding method, according to an embodiment of the present application.

[0062] Figure 2A and Figure 2B are respectively a perspective view of a plastic honeycomb catalyst industrial product, for example prepared by a thermoplastic molding method, according to an embodiment of the present application.Figure 2A ), and a cross-sectional schematic view (b) showing the presence of a large number of pore structures in the flue gas channel of the thermoplastic honeycomb catalyst product. Figure 2B Figure 2B The presence of a large number of pore structures in the flue gas channel of the thermoplastic honeycomb catalyst product is schematically shown.

[0063] Figure 3A A front view of a plate catalyst product prepared by a hot-pressing forming method according to an embodiment of the present application is shown.

[0064] Figure 3B A perspective view of a thermoplastic plate catalyst product prepared by a hot-pressing forming method according to an embodiment of the present application is schematically shown.

[0065] Figure 3C A schematic view of an activity evaluation device for testing and evaluating the catalytic activity of the honeycomb low-temperature SCR catalyst of the present application is schematically shown. Figure 3A An enlarged schematic view of a single thermoplastic plate catalyst of the thermoplastic plate catalyst product shown in (a) is shown, which shows the presence of a large number of pore structures on the surface of the plate catalyst.

[0066] Figure 4 A performance comparison of a PEEK-based catalyst prepared by a thermoplastic forming method according to an embodiment of the present application with an industrial catalyst is schematically shown.

[0067] Figure 5 A performance comparison of PEEK, PFA and PPS-based catalysts prepared by a thermoplastic forming method according to an embodiment of the present application with an industrial catalyst is schematically shown.

[0068] Figure 6 A performance comparison of different plastic-based catalysts prepared by a hot-pressing forming method according to an embodiment of the present application is schematically shown.

[0069] Figure 7 A performance test of a PEEK-based catalyst according to an embodiment of the present application and a PEEK-based catalyst after reforming after use is schematically shown.

[0070] Figure 8 Data of performance recovery of a PEEK-based catalyst after SO2 poisoning and regeneration according to an embodiment of the present application is schematically shown.

[0071] Figure 9 Data of performance recovery of a PEEK-based catalyst after SO2 poisoning and regeneration according to an embodiment of the present application is schematically shown.

[0072] Figure 10 Test results of a PEEK-based catalyst after multiple reforming and working at a predetermined reasonable working temperature according to an embodiment of the present application are schematically shown.​

[0073] Figure 11 An example of a hot press molding process for preparing a low temperature SCR catalyst of the present application according to an embodiment of the present application is schematically illustrated.

[0074] Figure 12 An example of a hot press molding process for preparing a low temperature SCR catalyst of the present application according to an embodiment of the present application is schematically illustrated.

[0075] Figure 13 An example of a hot extrusion molding process for preparing a low temperature SCR pellet catalyst of the present application according to an embodiment of the present application is schematically illustrated.

[0076] Figure 14 An example of a hot extrusion molding process for preparing a low temperature SCR honeycomb catalyst of the present application according to an embodiment of the present application is schematically illustrated.

[0077] Figure 15 An example of a fine SCR DeNOx catalyst system that is regenerable multiple times according to an embodiment of the present application is schematically illustrated, for illustratively showing and describing the system of the segmented catalyst (modules / segments) arrangement for fine SCR DeNOx of the present application and its general configuration. DETAILED DESCRIPTION

[0078] The details of one or more embodiments of the application are set forth in the description below. Other features, objects, and advantages of the application will be apparent from the description and drawings, and from the claims.

[0079] It should be understood that the illustrated and described embodiments are not limited in application to the details of construction and arrangement of parts illustrated in the following description or illustrated in the drawings. The illustrated embodiments can be capable of implementation in other embodiments and of being practiced or carried out in various ways. Indeed, it will be apparent to those skilled in the art that various modifications and variations can be made to the embodiments / examples of the application without departing from the scope or spirit of the application. For instance, features illustrated or described as part of one embodiment, can be used with another embodiment to yield still a further embodiment. Thus, it is intended that the present disclosure cover such modifications and variations as come within the scope of the appended claims and their equivalents.

[0080] Also, it is to be understood that the phraseology and terminology used herein is for the purpose of description and should not be regarded as limiting. The use of "including," "comprising" or "having" and variations thereof herein is meant to encompass the items listed thereafter and equivalents thereof as well as additional items.

[0081] The present application will be described in more detail below with reference to several specific embodiments of the present application.

[0082] Generally speaking, the working principle of selective catalytic reduction (SCR) De-NOx catalyst mainly involves the following steps:

[0083] (i) External diffusion process: the process of diffusion of nitrogen oxides and ammonia from the gas phase bulk to the outer surface of the catalyst;

[0084] (ii) Internal diffusion process: the diffusion of reactants from the outer surface of the catalyst to the inner surface so as to react at the active center;

[0085] (iii) Adsorption process: the adsorption of reactants at the active center;

[0086] (iv) Catalytic reaction: catalytic reduction reaction of adsorbed nitrogen oxides (NO x ) and ammonia at the active center of the catalyst and at a certain temperature to generate nitrogen and water;

[0087] (v) Desorption process: the desorption of reaction products from the active center; and

[0088] (vi) Internal diffusion process: the diffusion of reaction products from the active center to the outer surface through the inner surface of the catalyst after desorption.

[0089] Low-temperature SCR De-NOx systems generally include a device for storing and injecting a reducing agent (such as ammonia NH3 or urea CO(NH2)2), an SCR control unit, and an SCR catalyst. Urea is hydrolyzed and decomposed to generate ammonia. At a suitable low-temperature condition (generally about 200-300°C or below), ammonia-selective catalytic reduction (NH3-SCR) agents can directly catalyze the reaction of nitrogen oxides (NO x ) in flue gas with ammonia to generate harmless nitrogen and water, while harmful flue gas particles can also be absorbed. The corresponding reaction formula is as follows:

[0090] CO(NH2)2+ H2O = CO2↑+ 2NH2↑

[0091] 4NH3+ 4NO + O2 = > 4N2+ 6H2O

[0092] 4NH3+ 2NO2+ O2 = > 3N2+ 6H2O

[0093] In terms of conventional technology, TiO2-based catalysts gradually replace Pt-Rh and Pt series catalysts. The composition of such catalysts mainly includes V2O5 as the main active component and WO3, MoO3 as the anti-oxidation and anti-poisoning auxiliary components, for example, mainly composed of V2O5(WO3), Fe2O3, CuO, CrO x , MnO xMetal oxides such as TiO2, Al2O3, ZrO2, SiO2, activated carbon (AC), etc. or a mixture thereof as a carrier, and a reducing agent such as liquid ammonia or urea in the SCR system to form a reducing reaction, which is the mainstream catalyst product for power plant SCR denitration engineering applications.

[0094] The inventors of the present application found that in the field of catalysts, polymer-supported nanocatalyst particles as carrier materials can be regenerated and reused, which makes it possible for the nanocatalyst particles after service to be regenerated and reused in new or regenerated catalysts. This recyclable feature makes it possible for the pollutants generated during the production of catalysts not to flow back into the environment to cause pollution. The organic polymer carrier (or base, skeleton, etc.) of the catalyst has a relatively low degree of active site exposure due to its small surface area, and therefore needs to add other aids to help generate a large number of pore structures to increase its specific surface area. In addition, this method accelerates the diffusion of water out of the catalyst, which helps to achieve high activity and long-term stability of the catalyst.

[0095] One of the main ideas of the present application is to preferably use a hydrophobic organic polymer, especially a hydrophobic thermoplastic, as a carrier skeleton for low-temperature SCR catalysts, which on the one hand can achieve the above technical advantages and can be technically applied to the application occasions of low-temperature SCR catalysts (here "low-temperature" refers to the normal working temperature of the SCR catalyst generally below 300°C, more preferably below 250°C), and on the other hand the thermoplasticity of such plastics makes it possible to realize the large-scale process method of reshaping and regeneration of the low-temperature SCR catalyst.

[0096] Of course, those skilled in the art can understand that using thermoplastic plastics (such as but not limited to PPS, PEEK, PBT, etc.) as low-temperature SCR catalyst carrier / base material can achieve more technical advantages and benefits, including but not limited to: easy to clean, crush, process and reshape after sulfur (for example, SO2) poisoning and deactivation (ammonium sulfate deposition); can be easily used in a wide range of application environments including low ash areas, and is easy to clean and regenerate; the characteristics of thermoplastic plastics make the low-temperature SCR catalyst product lightweight, easy to transport and install, and less brittle, which is not easy to damage during transportation, installation and use; wide availability, easy availability and low cost of material sources; non-toxicity and environmental friendliness of the material; extremely high yield (theoretical yield 100%, no inferior products); extremely high recycling rate (theoretical recycling rate close to 100%).

[0097] The inventors of the present application have found that the carrier / base material suitable for low-temperature SCR catalysts can be selected to use a thermoplastic plastic material with relatively high plasticizing forming temperature (e.g. its forming temperature is generally above about 200℃) as the carrier skeleton forming agent, such as but not limited to PBI; PI; TPI; PAI; PEEK; PPS; PTFE; PFA; ETFE; PCTFE, etc. The normal working temperature of such thermoplastic plastic-based “low-temperature” SCR catalyst is generally below 300℃, more preferably below 250℃.

[0098] The forming process of thermoplastic plastic material in the preparation of low-temperature SCR catalysts of the present application can include but is not limited to: thermoforming, hot-press forming, extrusion forming, 3D printing forming, electrostatic spinning forming, spray forming, injection forming, die forming, blow forming, calendering forming, rotational molding forming, vacuum forming (suction forming), casting forming (injection forming), slush molding forming, flow casting forming, foaming forming, transfer molding forming (compression molding), winding forming, etc.

[0099] The shape (configuration) of the low-temperature SCR catalysts of the present application after preparation can include but is not limited to: honeycomb catalyst products, plate catalyst products, corrugated plate catalyst products, tubular catalyst products, rod catalyst products, granular catalyst products, mesh catalyst products, porous solid foam catalyst products, etc. According to the above concepts and features of the present application, these catalyst products can be reformed and regenerated after use.

[0100] According to the concept of one aspect of the present application, the thermoplastic forming of the low-temperature SCR catalysts of the present application can effectively perform rapid thermoplastic forming with polymeric thermoplastic as the carrier material of the catalyst; the combination effect is better after adding catalyst powder (which can act as a binder), and the forming effect is better; the large number of pore structures generated during the thermoplastic process can make the formed catalyst have a larger specific surface area, thereby improving the catalytic activity; the performance of the catalyst is directly related to the content of the catalyst during the forming process, and the thermoplastic formed low-temperature SCR catalysts of the present application have a larger proportion of catalyst components, so their catalytic performance is better than existing catalysts under the same test conditions.

[0101] The thermoplastic polymer materials suitable for the low-temperature SCR catalysts of the present application in thermoplastic forming and extrusion forming include: PEEK, PFA, PPS, PTFE, PBT, PEI, PES, PCTFE, ETFE, PAI, PBI, PI, FEP, PPA, PSU, PPSU, PE, PP, fluororubber (FKM), silicone rubber (VMQ), nylon (PA), etc. These materials are all polymer materials with rapid thermoplastic ability and stable physical and chemical properties.

[0102] In the present embodiment, the catalyst powder used is selected from catalyst materials with good low-temperature denitration performance, such as: Mn / Ce low-temperature denitration catalyst, V-based catalyst, Cu-based catalyst, etc.

[0103] For detailed introduction of the Mn / Ce low-temperature denitration catalyst and related content of the formula, please refer to the Chinese Invention Patent Application CN117019136A filed by the inventor of the present application on July 28, 2023, which is incorporated herein by reference.

[0104] Examples of low temperature SCR catalysts

[0105] Figure 1A and Figure 1B and Figure 2A and Figure 2B The present application illustrates the catalyst product prepared by the thermoplastic molding method. Among them, Figure 1A and Figure 1B are respectively the honeycomb catalyst product and the granular catalyst product prepared by the thermoplastic molding method according to an embodiment of the present application. Figure 2A and Figure 2B are respectively the perspective view ( Figure 2A ) and the cross-sectional view ( Figure 2B ) of the plastic honeycomb catalyst industrial product prepared by the thermoplastic molding method according to an embodiment of the present application, wherein Figure 2B illustrates that there are a large number of pore structures in the flue gas channel of the thermoplastic honeycomb catalyst product, which are formed by the added pore-forming agent. Those skilled in the art can understand that, as mentioned above, the low-temperature SCR catalyst (including but not limited to honeycomb) mentioned in the present application can also be implemented by the hot extrusion molding process disclosed in the present application, and is not limited to the thermoplastic molding, hot pressing molding, etc.

[0106] Thermo plastic molding of low temperature SCR catalysts

[0107] Figure 11 illustrates an example of the thermoplastic molding process for preparing the low-temperature SCR catalyst of the present application according to an embodiment of the present application.

[0108] The following takes PEEK material as an example, combined with the attached Figure 11 , to further introduce the thermoplastic molding process of the low-temperature SCR catalyst of the present application.

[0109] 1) Mix 200 mesh Mn / Ce catalyst powder (8 parts by weight) with PEEK powder (20 parts by weight), add NaCl, CaSO4, (NH4)2CO3, carbon powder, etc. as pore-forming agent (10 parts by weight), mix thoroughly and place in a cylindrical stainless steel mold.

[0110] 2) Seal the stainless steel mold with a stainless steel press, put it into a muffle furnace to heat up, plasticize and form at 200-400°C, preferably at 300-320°C, under a pressure of about 10.0 MPa for 6 hours.

[0111] 3) After water cooling, soak for 1-24 hours to remove the pore-forming agent, dry to obtain a cake-shaped thermoplastic formed catalyst, and process the obtained catalyst on a numerical control machine tool to obtain a honeycomb-shaped low-temperature SCR catalyst product, for example as shown in Figure 1A and Figure 2A and Figure 2B

[0112] Thermo extrusion molding of low temperature SCR catalysts

[0113] Next, taking PEEK material as an example, the hot extrusion molding process of the low-temperature SCR catalyst of the present application is further introduced.

[0114] 1) Mix 200-mesh Mn / Ce catalyst powder (8 parts by weight) with PEEK powder (20 parts by weight), add NaCl, CaSO4, (NH4)2CO3, carbon powder, etc. as pore-forming agents (10 parts by weight), and mix thoroughly to form an extrudable mixture;

[0115] 2) Load the mixture into the hopper of the extrusion molding machine, and set the heating temperature of the extrusion molding machine to 320°C to form a molten mixture;

[0116] 3) Extrude the molten mixture through the die opening of the extrusion molding machine to form an elongated catalyst rod of the required cross-sectional size and shape, and perform water cooling;

[0117] 4) After water cooling, soak in a cleaning solution for 1.5 hours to remove the pore-forming agent, dry, and cut to obtain granular low-temperature SCR catalyst of the required size and size, for example as shown in Figure 1B The cleaning solution is one or more of ammonia, water, sodium bicarbonate, ammonium carbonate, and trisodium phosphate solution, and the solution pH should be maintained at 5-8, and the sodium bicarbonate solution is preferably pH 7.5.

[0118] Figure 13 The hot extrusion molding process for preparing the low-temperature SCR granular catalyst of the present application according to an embodiment of the present application is schematically shown.

[0119] Next, taking PFA material as an example, the hot extrusion molding process of the low-temperature SCR catalyst of the present application is further introduced, as shown in the accompanying Figure 13 The hot extrusion molding process steps of the low-temperature SCR catalyst of the present application are as follows:

[0120] ​1) Mix 200 mesh Mn / Ce catalyst powder (8 parts by weight) with PFA powder (20 parts by weight), add NaCl, CaSO4, (NH4)2CO3, carbon powder, etc. as pore-forming agents (10 parts by weight), and mix thoroughly as a hot extrusion molding mixture;

[0121] 2) Load the mixture into the hopper of an extrusion molding machine, set the heating temperature of the extrusion molding machine to 350°C, and form a molten mixture;

[0122] 3) Extrude the molten mixture through the die opening of the extrusion molding machine to form an elongated catalyst rod of the desired cross-sectional size and shape, and perform water cooling;

[0123] 4) After water cooling, soak in a cleaning solution for 1.5 hours to remove the pore-forming agents, dry, and cut to size using a cutting device to obtain a granular low-temperature SCR catalyst of the desired size and dimensions, for example as shown in FIG. 1. Figure 1B The cleaning solution is one or more of ammonia, water, sodium bicarbonate, ammonium carbonate, and trisodium phosphate solution, and the solution pH should be maintained at 5-8, with a sodium bicarbonate solution preferably having a pH of 7.5.

[0124] Figure 14 Another hot extrusion molding process example for preparing the low-temperature SCR honeycomb catalyst of the present application according to an embodiment of the present application is schematically shown.

[0125] The following further introduces a hot extrusion molding process step example for the low-temperature SCR catalyst of the present application using PFA material as an example, in combination with FIG. 2. Figure 14

[0126] 1) Mix 200 mesh Mn / Ce catalyst powder (8 parts by weight) with PFA powder (20 parts by weight), add NaCl, CaSO4, (NH4)2CO3, carbon powder, etc. as pore-forming agents (10 parts by weight), and mix thoroughly as a hot extrusion molding mixture;

[0127] 2) Load the mixture into the hopper of an extrusion molding machine, set the heating temperature of the extrusion molding machine to 350°C, and form a molten mixture;

[0128] 3) Extrude the molten mixture through the honeycomb die opening of the extrusion molding machine to form a honeycomb catalyst of the desired number and size of channels, and immediately perform water cooling;

[0129] 4) After water cooling, soak in a cleaning solution for 1.5 hours to remove the pore-forming agents, dry, and cut to size using a cutting device to obtain a honeycomb low-temperature SCR catalyst of the desired length, for example as shown in FIG. 2. Figure 1A ​The cleaning solution is one or more of ammonia, water, sodium bicarbonate, ammonium carbonate, and trisodium phosphate solution, and the solution pH should be maintained at 5-8, and the pH of the sodium bicarbonate solution is preferably 7.5.

[0130] Thermo compression molded low temperature SCR catalysts

[0131] Figure 3A A front view of a plate catalyst product prepared by a hot-pressing method according to an embodiment of the present application is shown. Figure 3B A perspective view of a thermoplastic plate catalyst product prepared by a hot-pressing method according to an embodiment of the present application is shown schematically. Figure 3C A perspective view of a thermoplastic plate catalyst product prepared by a hot-pressing method according to an embodiment of the present application is shown schematically. Figure 3A A photo of a single thermoplastic plate catalyst of the thermoplastic plate catalyst product shown, showing that there are a large number of pore structures on the surface of the plate catalyst.

[0132] The thermoplastic polymer materials suitable for use in hot-pressing of the low-temperature SCR catalyst of the present application include, but are not limited to, ETFE, PFA, FEP, PPS, PBT, PBI, PEI, PSU, PEEK, fluoroelastomer (FKM), silicone rubber (VMQ), nylon (PA), etc. These polymer materials are selected to have a suitable softening temperature, almost no flow in the molten state, good surface wettability, and stable physical and chemical properties.

[0133] Figure 12 A hot-pressing process example for preparing the low-temperature SCR catalyst of the present application by a hot-pressing method according to an embodiment of the present application is shown schematically.

[0134] The following takes FEP material as an example, and the hot-pressing process of the low-temperature SCR catalyst of the present application is further introduced in combination with the accompanying drawings. Figure 12 The hot-pressing process of the low-temperature SCR catalyst of the present application is shown, and the hot-pressing process of the low-temperature SCR catalyst of the present application is further introduced.

[0135] 1) FEP emulsion (3 parts by weight) is mixed with catalyst powder (e.g., Mn / Ce low-temperature denitration catalyst, 10 parts by weight) to obtain mixed powder, which is coated on both sides of a (e.g., FEP) thermoplastic plastic plate to obtain a blank, the blanks are separated by a polyimide film, and the two ends are covered with stainless steel plates and placed on a hot press;

[0136] 2) Hot-pressing is performed in two stages on the hot press, and the specific parameters of the hot-pressing process are as follows:

[0137] The hot-pressing temperature of the first stage is 120-200°C, the hot-pressing pressure of the first stage is 50-80 Kg / cm 2 , and the hot-pressing time is 180 seconds (s);

[0138] The hot-pressing temperature of the second section is 200-300°C, and the hot-pressing pressure of the second section is 50-80 Kg / cm 2 The hot-pressing time is 180 seconds.

[0139] 3) After the hot-pressing, the shaped catalyst is cooled to room temperature, washed and dried, the partition is opened, and the shaped plate catalyst product is obtained, such as Figures 3A-3C as shown schematically.

[0140] Those skilled in the art can understand that in the above process step 1), according to the needs of the target application and performance, a certain proportion of pore-forming agents such as NaCl, CaSO4, (NH4)2CO3, carbon powder, etc. can be selectively added to the above mixture.

[0141] Regeneration of low temperature SCR catalysts

[0142] An important inventive concept and key advantage of the present application is that the low-temperature SCR catalyst of the present application can be conveniently regenerated by a reshaping (reforming) process.

[0143] Hereinafter, taking the PEEK-based low-temperature SCR catalyst of the present application as an example, the process method for regenerating the low-temperature SCR catalyst of the present application is further introduced.

[0144] 1) The deactivated (for example, deactivated due to sulfur poisoning) PEEK-based thermoplastic shaped catalyst is selectively washed first, for example, the surface fly ash and ammonium sulfate salt deposits are washed away by ultrasonic cleaning, dried and then put into a clean crusher for crushing treatment, for example, after crushing, the regenerated powder for reshaping is obtained after passing through a 10-mesh sieve.

[0145] 2) A suitable proportion of pore-forming agents (which can refer to the previous examples) is added to the above regenerated powder, and after being mixed thoroughly, it is placed in a mold.

[0146] The pore-forming agents are, for example, NaCl, CaSO4, (NH4)2CO3, carbon powder, etc., and the addition proportion can be, for example, 10%-150% by weight of the regenerated powder. The addition proportion of an example NaCl is, for example, between 50%-120% by weight of the regenerated powder.

[0147] 3) The mixed powder is added to a cylindrical mold, the mold is sealed with a press and placed in a muffle furnace for heating and thermoplastic shaping, and the hot-pressing plasticization shaping is carried out at a temperature range of 200-400°C, preferably at a heating temperature of 300-320°C, under a pressure of 1 MPa-5 MPa for 2-12 hours. If the particles of the regenerated powder are larger, the shaping time of the reshaping process step can be appropriately extended.

[0148] 4) After hot plastic forming, the mold is water-cooled / air-cooled for cooling, and after cooling to room temperature, the catalyst is taken out of the mold, and water-cooled again, and after completely cooling to room temperature, it is taken out and transferred to a cleaning solution to wash away the pore-forming agent, wherein the soaking time in the cleaning solution is 1-12 hours, and the cleaning solution can be one or more of ammonia, sodium bicarbonate, ammonium carbonate, and trisodium phosphate solution, and the solution pH value can be maintained at 5-8. After that, punching processing is performed on the numerical control machine tool to obtain a honeycomb-shaped low-temperature SCR catalyst.

[0149] In this regard, those skilled in the art can understand that in the above process step 1), a certain proportion of catalyst powder (for example, 10% of Mn / Ce powder) and / or PEEK powder can be selectively supplemented in the above regenerated powder to make up for possible composition and performance loss. Of course, this is not necessary, and test studies have shown that without supplementing catalyst and / or polymer powder, the low-temperature SCR catalyst of the present application can still be successfully remolded and regenerated without substantially affecting its catalytic performance. Experimental data show that the denitration efficiency of the low-temperature SCR catalyst of the present application after regeneration is comparable to that of existing industrial catalysts, and its activity can be maintained at least 80% or more, as described in detail below.

[0150] Those skilled in the art can understand that the above honeycomb-shaped low-temperature SCR catalyst can be remolded into other shapes as needed during remolding and regeneration, such as rod-shaped, pellet-shaped low-temperature SCR catalysts, etc., and does not necessarily have to be remolded into a honeycomb-shaped low-temperature SCR catalyst.

[0151] Those skilled in the art can also understand that the remolding and regeneration of the above low-temperature SCR catalyst is not limited to the hot plastic forming process, but can be performed using other suitable and applicable process methods other than hot plastic forming, such as but not limited to: hot press forming, hot extrusion forming, 3D printing forming, electrospinning forming, spray forming, cold extrusion forming, die forming, blow molding, calendering, rotational molding, vacuum forming (blow molding), casting (injection molding), slush molding, flow casting, foaming, press injection molding, winding molding, etc., which can be determined according to the material type of the thermoplastic plastic skeleton, the catalyst active ingredient and parameters, the shape of the required low-temperature SCR catalyst, the needs of the application site, etc., such as using the hot extrusion forming process described in the present application, etc.

[0152] Fine SCR De-NOx catalyst system regenerable multiple times and operation thereof

[0153] Figure 15An example of a regenerable fine SCR denitrification catalyst system according to an embodiment of this application is illustrated to demonstrate and describe the system and general configuration of the segmented catalyst (module / segment) arrangement of this application for fine SCR denitrification.

[0154] According to this embodiment, a low-temperature selective catalytic reduction (SCR) system for flue gas denitrification is introduced, which includes the low-temperature SCR catalyst of this application, such as a catalyst module prepared by thermoplastic molding and extrusion molding processes.

[0155] The fine SCR denitrification catalyst system of this application has better performance in terms of low-temperature SCR catalyst molding process, catalytic activity and mechanical strength, such as providing higher catalytic activity and better mechanical strength.

[0156] In this embodiment, the fine SCR denitrification catalyst system can be composed of several main parts:

[0157] (1) Replaceable catalyst module: a regenerable low-temperature SCR denitrification catalyst product that may contain multiple (e.g., multilayer) spaced apart from each other, such as plate-shaped, honeycomb-shaped and / or granular catalysts of the present application, for providing segmented / staged low-temperature SCR denitrification processes, such as below 300°C.

[0158] Preferably, as described above, the regenerable low-temperature SCR denitration catalyst may include: a support framework formed of thermoplastic plastic; and a low-temperature SCR denitration catalytic active component composited in and supported by the support framework. This refined SCR denitration catalyst system is configured to facilitate the removal and replacement of deactivated catalyst modules with new and / or regenerated catalyst modules. The regenerated catalyst module is obtained by removing the regenerable low-temperature SCR denitration catalyst from the deactivated catalyst module, regenerating it, and then reloading it. This regenerable low-temperature SCR denitration catalyst can be regenerated by remolding the thermoplastic support framework.

[0159] For example, multiple catalyst module segments include at least two of plate catalyst module segments, honeycomb catalyst module segments, and granular catalyst module segments.

[0160] According to a preferred example, the segmented catalyst module is arranged sequentially along the flue gas flow direction, consisting of a plate catalyst module segment, a honeycomb catalyst module segment, and a granular catalyst module segment. Following this order, as the flue gas flows through the plate catalyst module segment, the honeycomb catalyst module segment, and the granular catalyst module segment in sequence, due to the internal structure of these three catalyst module segments, the flue gas velocity naturally decreases sequentially, thereby removing, gradually and effectively, nitrogen oxides (NOx) from the flue gas according to these three catalyst module segments. x ), reduce NOx The content, realizing the segmented fine denitration.

[0161] (2) Reactor: used to accommodate catalyst modules and provide a suitable SCR denitration reaction environment.

[0162] The reactor can generally be made of stainless steel (such as 316L or 304) or carbon steel (surface coated with high-temperature resistant anticorrosive coating), and has a cylindrical or cuboid shape, with specific dimensions designed according to the flue gas treatment capacity (for example, diameter 2-5 meters, length 5-15 meters). Multiple layers of catalyst modules can be arranged inside the reactor (for example, according to the design of the flue gas flow direction, plate catalyst modules, honeycomb catalyst modules, and granules are arranged in sequence), and the thickness of the catalyst layer can be 300-500 mm or more, and the spacing between layers can be 50-100 mm, to optimize the airflow distribution and reaction efficiency. A homogenizer (such as a flow guide plate or a static mixer) can be configured at the inlet of the reactor to ensure uniform mixing of flue gas and ammonia; a pressure balancing device can be provided at the outlet to avoid airflow disturbance.

[0163] The reactor can be equipped with a flue gas temperature regulation system (such as a heat exchanger or a heater) to maintain the reaction temperature in the range of, for example, 200-300°C, to meet the needs of low-temperature SCR catalysts.

[0164] The reactor can be equipped with temperature sensors (such as thermocouples or infrared thermometers) and pressure sensors to monitor the operating state in real time and automatically adjust through the control system.

[0165] For example, commercially available reactors include the SCR-EE-LA / UR type reactor produced by Hebei Chengyue Environmental Engineering Co., Ltd., which supports low-temperature denitration and is suitable for boiler flue gas treatment due to its modular design; the double-path vertically arranged reactor produced by Shandong Shoufeng Intelligent Environmental Protection Equipment Co., Ltd., which can be used in various dust flue gas conditions; the honeycomb catalyst integrated reactor provided by Yuanchen Environmental Protection Technology Co., Ltd., and so on.

[0166] (3) Injection system: used to inject reducing agents (such as ammonia water or urea solution) into the reactor.

[0167] The injection system can generally include:

[0168] - Ammonia / ammonia water injection system: the nozzle can be made of stainless steel (such as 316L) or ceramic, and can have a multi-hole atomizing type or a fan-shaped injection type, with a pore size of 0.5-2 mm and an adjustable injection angle of 30-90°, to ensure sufficient mixing of ammonia and flue gas. The nozzles can be uniformly distributed along the flue cross-section, with a spacing of, for example, 200-500 mm, and the injection direction can be arranged in counterflow or parallel flow with the flue gas flow direction to enhance the mixing effect; the injection pressure and flow rate of ammonia / ammonia water: working pressure 0.3-0.8 MPa, flow rate range 50-500 L / min (which can be adjusted according to the flue gas NOx Concentration dynamic adjustment); and

[0169] - Ammonia supply and storage system, which can include a storage tank and a delivery device. The storage tank may, for example, be a stainless steel tank with a volume of 10-50 m 3 3and equipped with a liquid level meter, a safety valve and a leakage detection device, designed pressure 1.5 MPa. The delivery device may, for example, use a corrosion-resistant centrifugal pump (such as Grundfos CR series) or a screw pump with a flow accuracy of ±2%, supporting PLC remote control.

[0170] Examples of commercially available injection systems include, for example, SNCR-EE-LA / UR type provided by Hebei Chengyue Environmental Engineering Co., Ltd., equipped with high-pressure atomizing nozzles and a redundant safety system; "double-path ammonia injection system" (adapted to high-dust flue gas) of Shandong Shoufeng Intelligent Environmental Protection Equipment Co., Ltd., etc., which can integrate a steam carrier gas device to enhance penetration.

[0171] (4) Optional control system: for monitoring and / or adjusting the SCR reaction conditions, such as temperature, pressure and reducing agent injection amount, etc.

[0172] The control system can be either a component of the fine SCR denitration catalyst system or integrated into the control system of the application site or equipment of the fine SCR denitration catalyst system, such as a factory, a workshop, a waste gas treatment section, a ship, a car, etc.

[0173] As an example, the control system can be an automation system based on PLC (such as Siemens S7-1200), integrating an ammonia flow meter (such as a mass flow meter), a NO x concentration sensor (such as an ultraviolet analyzer) and a temperature feedback module to achieve closed-loop control of the ammonia nitrogen molar ratio (NH3 / NO x ) (target value 0.8-1.2). In addition, an ammonia shut-off valve (such as an ASCO solenoid valve) can be triggered in an emergency, with a response time <1 second.

[0174] In this embodiment, the general operation of the fine SCR denitration catalyst system is as follows:

[0175] (1) System startup: After the system is started, the control system can automatically or manually adjust the reaction condition parameters in the reactor, such as reaction temperature, pressure, reducing agent injection amount, etc., according to the flue gas conditions.

[0176] (2) SCR catalytic denitration reaction: The injection system injects reducing agent into the reactor, which reacts with NO x in the flue gas on the surface of the low-temperature SCR catalyst in this application to generate nitrogen and water.

[0177] (3) Monitoring and adjustment: the control system monitors the reaction efficiency in real time, and adjusts the reaction conditions such as reaction temperature, pressure, reducing agent injection amount, and / or reaction time as needed.

[0178] (4) Regeneration of the fine SCR De-NOx catalyst system: after a period of time, or a predetermined period of use, the low-temperature SCR De-NOx catalyst product is removed from the catalyst module, and the low-temperature SCR De-NOx catalyst is subjected to the reshaping regeneration treatment according to the regeneration method of the present application (for example, the regeneration of the low-temperature SCR catalyst is described above), the regenerated low-temperature SCR catalyst is reinstalled into the catalyst module, thereby completing the regeneration of the fine SCR De-NOx catalyst system. Thus, the regenerated fine SCR De-NOx catalyst system can be reused and used normally.

[0179] More specifically, according to an example, the recycling method of the fine SCR De-NOx catalyst system that can be regenerated multiple times can include the following steps: removing the deactivated catalyst module from the reactor; pre-treating the low-temperature SCR De-NOx catalyst of the deactivated catalyst module before regeneration; reshaping the pre-treated low-temperature SCR De-NOx catalyst, which can be regenerated at the same time; and loading the regenerated low-temperature SCR De-NOx catalyst back into the catalyst module, and then reinstalling the catalyst module back into the reactor, thereby realizing the recycling of the fine SCR De-NOx catalyst system.

[0180] The pre-treatment can include the following steps: crushing the low-temperature SCR De-NOx catalyst of the deactivated catalyst module to obtain regenerated powder in a desired size range. Before or after the crushing treatment, the low-temperature SCR De-NOx catalyst of the deactivated catalyst module can be washed. After the crushing treatment, a screening treatment can also be performed.

[0181] The regenerated fine SCR De-NOx catalyst system of the present embodiment uses the reshaped and regenerated low-temperature SCR De-NOx catalyst of the present application, has lower cost, very simple and efficient reshaping and regeneration process, almost 100% recyclability, almost no loss of catalytic activity, and better mechanical strength than existing catalyst products, can be effectively reused to reduce NOx emissions in flue gas, reduce energy consumption, reduce pollution, reduce waste, reshape and regenerate, low maintenance cost, lightweight catalyst (module) and convenient installation and transportation, etc., and meet strict environmental protection and regulatory requirements. x

[0182] Testing and evaluation of low temperature SCR catalysts

[0183] Figure 4 ​A schematic diagram of an activity evaluation device for testing and evaluating the catalytic activity of the honeycomb low-temperature SCR catalyst of the present application is shown schematically. Through the activity evaluation device, the catalytic activity of the honeycomb low-temperature SCR catalyst of the present application containing MnO x / CeO2 catalyst components can be tested and evaluated, wherein the reaction gas can be mixed in a gas mixing tank via a mass flow meter to control the gas flow, and after the catalytic reaction treatment of the low-temperature SCR catalyst of the present application, the flue gas NO x content at the tail gas end can be tested.

[0184] Figure 5 The performance comparison of the PEEK catalyst (i.e., the PEEK-based low-temperature SCR catalyst of the present application) prepared by the thermoforming method according to an embodiment of the present application and the industrial catalyst is shown schematically. In the test, the test carrier gas is N2, the gas flow rate is 2.1 m / s, NO: 500 ppm, NH3: 500 ppm, O2: 5%, and the volume space velocity GHSV is 6000 h -1 The test results of the catalytic activity performance of the PEEK catalyst, the industrial small-scale catalyst, and the industrial catalyst under the same size and the same test conditions are shown. The test results show that the low-temperature SCR catalyst prepared by using PEEK plastic as the carrier material has high catalytic activity and is close to the performance of the industrial catalyst.

[0185] Figure 6 The performance comparison of the PEEK, PFA, and PPS-based catalysts prepared by the thermoforming method according to an embodiment of the present application and the industrial catalyst is shown schematically. In the test, the test carrier gas is N2, the gas flow rate is 2.1 m / s, NO: 500 ppm, NH3: 500 ppm, O2: 5%, and the volume space velocity GHSV is 6000 h -1 The test results of the performance of the catalysts prepared by the thermoforming of different materials and the industrial catalyst under the same size and the same test conditions are shown. The content in the brackets after the material indicates the mass ratio of the catalytic active component in the carrier material. It can be seen that the catalytic performance of the formed catalyst prepared by using PEEK and PFA materials as the base materials and the industrial catalyst is almost the same in the temperature range of 150℃ to 200℃.

[0186] Figure 7 The performance comparison of different plastic-based catalysts prepared by the hot-pressing forming method according to an embodiment of the present application is shown schematically. In the test, the test carrier gas is N2, the gas flow rate is 2.1 m / s, NO: 500 ppm, NH3: 500 ppm, O2: 5%, and the volume space velocity GHSV is 1500 h -1The performance of the plate catalysts of the present application prepared according to three different catalyst skeleton materials is close to that of the performance of the industrial application catalysts.

[0187] Figure 8 The SO2 poisoning performance test results of the PEEK-based catalyst according to an embodiment of the present application and the PEEK-based catalyst after remolding after use are schematically shown. In the test, the test carrier gas is N2, the gas flow rate is 2.1 m / s, NO is 500 ppm, NH3 is 500 ppm, O2 is 5%, SO2 is 200 ppm, the gas hourly space velocity GHSV is 9000 h -1 In the comparative experiment, the running state of the molded catalyst prepared by taking the PEEK material as an example at a higher SO2 concentration of 200 ppm is tested, and the catalyst catalytic activity slightly decreases but is stabilized at about 80% and does not change any more in 24 h. After 24 h of testing, the catalyst is taken out, remolded, and the remolded catalyst is subjected to the same anti-poisoning experiment again. The results show that the catalyst performance still remains above 80% and does not decrease in the next 24 h SO2 poisoning test. This shows that the remolding process does not affect the catalyst activity.

[0188] Figure 9 The performance recovery data of the PEEK-based catalyst after SO2 poisoning and regeneration according to an embodiment of the present application are schematically shown.

[0189] Figure 10 The performance test results of the PEEK-based catalyst after multiple remolding and working at a predetermined reasonable working temperature according to an embodiment of the present application are schematically shown. A small amount of broken powder is inevitably lost in the remolding process, and therefore, catalyst powder or thermoplastic plastic powder can be appropriately added in the remolding process, so that the size of the remolded catalyst and the size before breaking are basically consistent. Generally, the amount of addition is preferably less than about 30% of the total catalyst amount before breaking, and too much addition of the active component will cause the specific gravity of the thermoplastic plastic material to be small, the adhesion between the active components to be weak, and the molding to be difficult.

[0190] Introduction of some technical effects of low temperature SCR catalysts

[0191] In the technical content of the present application, the thermoplastic material can be used as the carrier (or matrix, skeleton, carrier skeleton, etc.) material of the catalyst, replacing the existing TiO2 and other conventional materials, thereby simplifying the integrated forming process of the catalyst and the regeneration process (for example, by reshaping) of the catalyst. Using the polymer thermoplastic as the carrier material and the catalyst powder as the inorganic binder of the thermoplastic, the two are tightly combined during the thermoplastic forming process, improving the overall mechanical strength of the catalyst and avoiding the leaching of the active components of the catalyst; the addition of the pore-forming agent enables the monolithic catalyst to have more fine pore structures during preparation, thereby improving the specific surface area of the catalyst; using the thermoplastic as the base material enables the catalyst to be reused, and the regeneration process is simple and fast, which can avoid the energy waste and environmental pollution existing in the traditional regeneration process, and greatly prolongs the service life of the catalyst.

[0192] The experiments prove that the catalyst prepared by the preferred formula of the present application has similar denitration activity to the traditional industrial catalyst under the same size and test conditions at 200℃, 150℃ and 100℃; under the preferred catalyst formula of the present application, the catalyst can maintain a performance of more than 80% without decline under 200ppm SO2 for long-term continuous operation; after cleaning and reshaping the poisoned catalyst by the regeneration method introduced in the present application, the catalyst activity at 200℃, 150℃ and 100℃ is basically the same as that before reshaping; after reshaping the catalyst multiple times by the regeneration method introduced in the present application, the catalyst activity at 200℃, 150℃ and 100℃ is basically the same as that before the first reshaping.

[0193] The foregoing description of several embodiments of the present application is presented for the purpose of illustration. The foregoing description is not intended to be exhaustive or to limit the application to the precise steps and / or forms disclosed, since apparent modifications and variations are possible in light of the above teachings. The scope and spirit of the application are intended to be limited only by the claims appended hereto.

Claims

1. A method of extrusion molding of a regenerable low-temperature SCR catalyst, the low-temperature SCR catalyst comprising: a thermoplastic plastic forming a carrier skeleton of the low-temperature SCR catalyst; a low-temperature SCR catalytically active component dispersedly compounded in and supported by the carrier skeleton formed by the thermoplastic plastic; the method comprising the following steps: (1) mixing a low-temperature SCR catalytically active component powder with a thermoplastic plastic powder to obtain an extrudable mixture; (2) loading the mixture into an extrusion molding machine to melt and form a molten mixture; (3) extruding and molding the molten mixture through a matched die of the extrusion molding machine to obtain an extrusion molding blank; and (4) cooling the extrusion molding blank and optionally processing to obtain a molded low-temperature SCR catalyst, wherein the low-temperature SCR catalyst is capable of being regenerated by re-extrusion molding.

2. The method of claim 1, wherein, The temperature of the melting is in the range of 200-400°C, preferably 300-320°C.

3. The method of claim 1, wherein, The method further comprises a process of adding at least one of a pore-forming agent, a foaming agent and a plasticizer to the extrudable mixture in the step (1).

4. The method of claim 3, wherein, The pore-forming agent is selected from at least one of NaCl, CaSO4, (NH4)2CO3 and carbon powder.

5. The method according to any of the preceding claims, characterized in that, The method further comprises a step of cleaning the extrusion molding blank.

6. The method according to any of the preceding claims, characterized in that, The processing in the step (4) comprises cutting processing of the cooled extrusion molding blank.

7. The method according to any of the preceding claims, characterized in that, The shape of the molded low-temperature SCR catalyst has at least one of the following shapes: granular, plate-like, sheet-like, round pipe-like, round rod-like, square pipe-like, square rod-like and regular solid block-like.

8. The method according to any of the preceding claims, characterized in that, The method is suitable for extrusion molding of at least one of the following thermoplastic plastics: PEEK, PFA, PPS, PTFE, PBT, PEI, PES, PCTFE, ETFE, PAI, PBI, PI, FEP, PPA, PSU, PPSU, PE, PP, fluoro rubber (FKM), silicone rubber (VMQ) and nylon (PA).

9. The method according to any of the preceding claims, characterized in that, The method further comprises a step of regenerating the deactivated low-temperature SCR catalyst by re-extrusion molding.

10. The method according to claim 9, characterized in that The regenerating step comprises: pre-treatment of the deactivated low-temperature SCR catalyst before regeneration, the pre-treatment comprising cleaning and crushing to obtain an extrusion molding regeneration material; and re-extrusion molding of the extrusion molding regeneration material, wherein the regeneration of the deactivated low-temperature SCR denitration catalyst is achieved simultaneously with the re-extrusion molding.

11. The method of claim 9, wherein, The re-extrusion molding at least comprises the steps (1) to (4).

12. The method of claim 9 or 10, wherein, At least one of a low-temperature SCR catalytically active component powder, a thermoplastic plastic powder and a pore-forming agent or a foaming agent is supplemented in the mixture before the re-extrusion molding is performed.

13. The method according to any of the preceding claims, characterized in that, The carrier skeleton of the low-temperature SCR catalyst prepared by the extrusion molding method has a self-supporting configuration before and after the re-extrusion molding, thereby enabling the low-temperature SCR catalyst to have a self-supporting configuration without external support within a set working temperature range.

Citation Information

Patent Citations

  • Monolithic low-temperature manganese / cerium honeycomb denitration catalyst

    CN117019136A